Prototype of New Composite Weightage and Offset Thickness Design of Acetabular Cup in THR - Abd Manap, Muhammad Faris; Shuib, Solehuddin; Shaari, Nor Shamimi; Zainudin, Mahfuzah; Syafiq Khalid, Muhamad Faris (2020)
Defect bone at hip joint of human body will required surgical operation which commonly known as Total hip replacements (THR). Succession rate of the surgical procedures depending on many factors. Currently the THR operation could not guarantee 100% succession rate which dislocation, fracture, inflammation, edge-loading effect and rejection of new materials are among the concerned issues. The objective of this study particularly to make a prototype of new composite weightage and offsetting thickness of acetabular cup in order to increase the surgical post-operative succession rate. Firstly, a new design was drawn using SolidWorks software which the articulation area was offset by increasing the superior region. Then, the FE analysis conducted via ANSYS WORKBENCH to simulate the effect of offsetting the acetabular cup design. Secondly, a new material composition of Ep-UHMWPE with various weightage and thickness were studied experimentally according to ASTM D638-02A. Simulation and experimental analysis results show good agreement that 5mm thickness improvise mechanical properties up to 66% in term of Von-Mises stress, total deformation and contact pressure. Thus, offsetting superior region thickness could potentially improvise the implant lifespan especially during the normal gait condition. Adding Ep (Epoxy) into existing material (UHMWPE) at ideal weightage also increasing the mechanical properties of the acetabular cup. However, further studies are required to design a second prototype with higher articulation efficiency and material's biocompatibility.